PENGENDALIAN NON KIMIA SCHISTOSOMIASIS SECARA DINI PADA ANAK SEKOLAH DASAR DI KECAMATAN LINDU KABUPATEN SIGI, SULAWESI TENGAH - Syukur S, Djunaedil; Zainul, Zainul; Novarianti , Novarianti (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Lindu District is located in Sigi Regency, Central Sulawesi Province, this district is quite famous for its typical disease and the only one in Indonesia, namely snail disease/Schistosomiasis which is at an altitude of 1000 M above sea level with the presence of Lake Lindu. Located in the eastern part of Palu City and approximately 65.4 KM away, surrounded by mountains can be reached by 2 and 4 wheeled vehicles decorated with winding roads on the cliffs of mountain forests and ravines which are one of the national nature reserves. The purpose of this community service activity is to provide and improve knowledge and practical methods from an early age to prevent contact with the Schistosomiasis parasite in school residents in Lindu District. The approach method is by means of counseling, interactive discussions and technical guidance for elementary school children. The measuring instrument used is a questionnaire. Benefits to minimize and suppress the incidence of Schistosomiasis in children from an early age. The target of the activity is 100 elementary school children with a frequency of 2 exposure activities in Anca Village, Tomado Village and Langkoo Village from February to March 2025. The success parameters used are if knowledge reaches; > 85%. The conclusion can increase elementary school children's knowledge about Schistosomiasis prevention by 17% (from 26% to 43%), covering the target achievement of 65%. It is recommended that this activity can cover various age groups that are expected to receive sufficient funds, implemented continuously in the future.